Efficiency of sewage sludge biochar in improving urban soil properties and promoting grass growth. (April 2017) - Yue, Yan; Cui, Liu; Lin, Qimei; Li, Guitong; Zhao, Xiaorong
Abstract: It is meaningful to quickly improve poor urban soil fertility in order to establish the green land vegetation. In this study, a series rates (0%, 1%, 5%, 10%, 20% and 50%, in mass ratio) of biochar derived from municipal sewage sludge was applied into an urban soil and then turf grass was grown in pots. The results showed that biochar amendment induced significant increases in soil total nitrogen, organic carbon, black carbon, and available phosphorus and potassium by more than 1.5, 1.9, 4.5, 5.6 and 0.4 times, respectively. Turf grass dry matter increased proportionally with increasing amount of added biochar (by an average of 74%), due to the improvement in plant mineral nutrition. Biochar amendment largely increased the total amounts of soil heavy metals. However, 43–97% of the heavy metals in the amended soil were concentrated in the residual fraction with low bioavailability. So the accumulation of heavy metals in turf grass aboveground biomass was highly reduced by the addition of biochar. These results indicated that sewage sludge biochar could be recommended in the poor urban raw soil as a soil conditioner at a rate of 50%. However, the environmental risk of heavy metal accumulation in soil amended with sewage sludge biochar should be carefully considered. Highlights: Sewage sludge biochar could improve urban soil properties. Biochar could stimulate turf grass growth even at a rate of 50%. The plant uptake of heavy metals was the lowest at the application ratio of 5%.